Cardiac allograft vasculopathy after heart transplantation: Current state of knowledge on diagnosis and treatment Transplantatvaskulopathie nach Herztransplantation: Aktueller Wissensstand zu Diagnose und Therapie - Kuckhahn, Annika; Ramsperger-Gleixner, Martina; Ensminger, Stephan; Weyand, Michael; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2019)
Chronic rejection with its characteristic feature of cardiac allograft vasculopathy (CAV) is one of the major complications after successful heart transplantation and cannot be prevented by the currently used standard immunosuppressants. This review article describes the epidemiology of CAV and the pathogenesis of this multifactorial process that leads to the development of a neointima consisting mainly of vascular smooth muscle cells. Additionally, current diagnostic procedures for cardiac allograft vasculopathy are depicted. The diffuse distribution of vascular alterations combined with the mostly delayed development of clinical symptoms hampers the diagnosis of CAV. In the last few years various approaches for treatment and prevention of CAV were described and evaluated using preclinical models. An important animal model to investigate new options is abdominal aortic transplantation in mice. Such models demonstrated that cytomegalovirus infection is of great importance for CAV development. In addition, the administration of the platelet aggregation inhibitor clopidogrel, especially in combination with a mechanistic target of rapamycin (mTOR) inhibitor, could attenuate CAV formation. Moreover, ischemic preconditioning showed positive results. In some studies, the treatment with direct anti-proliferative substances achieved promising results to delay the development of CAV. The experimental approaches in animals need to be evaluated for safety and efficacy in clinical studies in order to improve postoperative long-term survival of heart transplantation patients in the future.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cytomegalovirus; Ischemic preconditioning; Neointima; Platelet aggregation inhibitors; Transplant rejection